Analisis Karakter Morfologi Beberapa Aksesi Bawang Merah (Allium cepa L. di Dataran Rendah Kabupaten Karawang - Camila Fatimatuzahra; Elia Azizah; Winda Rianti (Jurnal Agrotek Indonesia (Indonesian Journal of Agrotech), 2022)
The solution to increase the productivity of shallots in the lowlands of Karawang Regency is the use of appropriate accessions. To get the right accession, morphological analysis using various accessions is needed. The use of various accessions aims to find out the right accessions for planting in the lowlands of Karawang Regency. The research was carried out in the experimental field of the Faculty of Agriculture, Singaperbangsa Karawang University, which is located in Pasir Jengkol Village, Majalaya District, Karawang Regency. The study was conducted in December 2021 – March 2022. This study aimed to obtain shallot accessions that are well adapted to the lowlands of Karawang. The research method used an experimental method with a single factor randomized block design (RAK). There were 8 accessions, repeated 4 times, so there were 128 experimental plants. Data were analyzed using analysis of variance and further test with DMRT (Duncan Multiple Range Test) at 5% level. The results of this experiment showed that there were significant differences in the appearance of the morphological characters of shallot accessions (plant height, number of leaves, number of bulbs). Accession LKG1 (Lokal Karawang) gave the highest yield at plant height of 33.34 cm. Accession BLR7 (Blue Lancor) gave the highest yield on the number of leaves of 40.19 strands, and the number of bulbs of 13.00 cloves.